Progress in the Rational Design for Polypharmacology Drug - Zhou, Jinming; Li, Quanjie; Wu, Meng; Chen, Chao; Cen, Shan (Current Pharmaceutical Design, 2016)
Background: Polypharmacology plays an important role in drug discovery. Polypharmacology drugs strategy provides a novel way in drug design. However, to develop a polypharmacology drug with desired profile remains a challenge. Methods: Owing to the huge progress in computational biology and chemistry, the rational drug design is becoming increasingly important in discovery of polypharmacology drug. Results: Several methodologies on the rational polypharmacology drug design have been developed, which are summarized and classified as ligand based design in polypharmacology, target based design in polypharmacology, and the hybrid of ligand and target based design in polypharmacology. Conclusion: We give an overview of the importance of polypharmacology in drug design and current trends in rational design of polypharmacology, which may be beneficial to the design and development of polypharmacology drugs.
Keywords: Multiple ligand